EDEN ISS - greenhouse in Antarctica - Vrakking, Vincent; Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Dorn, Markus; Ferl, Robert; Paul, Anna-Lisa (2020)
Ant-Land Status Report describing activities and preliminary results of the 2019 Antarctic winter season and the 2019/20 Antarctic summer season